Glycolate Pathway in Green Algae - Bruin, W. J. (1970)
By three criteria, the glycolate pathway of metabolism is present in unicellular green algae. Exogenous glycolate-1-(14)C was assimilated and metabolized to glycine-1-(14)C and serine-1-(14)C. During photosynthetic (14)CO(2) fixation the distributions of (14)C in glycolate and glycine were similar enough to suggest a product-precursor relationship. Five enzymes associated with the glycolate pathway were present in algae grown on air. These were P-glycolate phosphatase, glycolate dehydrogenase (glycolate:dichloroindophenol oxidoreductase), l-glutamate:glyoxylate aminotransferase, serine hydroxymethylase, and glycerate dehydrogenase. Properties of glycerate dehydrogenase and the aminotransferase were similar to those from leaf peroxisomes. The specific activity of glycolate dehydrogenase and serine hydroxymethylase in algae was 1/5 to 1/10 that of the other enzymes, and both these enzymes appear ratelimiting for the glycolate pathway. Labeling patterns for products of the glycolate pathway during (14)CO(2) fixation are not the same as those obtained with higher plants. In higher plants glycolate, glycine, and serine are uniformly labeled at shortest time periods. In algae, serine was predominately carboxyl-labeled, similarly to 3-phosphoglycerate. This result, plus the lower specific activity of serine hydroxymethylase, indicates that the glycine-serine interconversin in algae is slower than in plants. Initially (2 to 4 seconds) glycolate and glycine were more C-2 labeled. They rapidly became uniformly labeled, with glycine becoming uniformly labeled first. In the presence of isonicotinylhydrazide, labeled glycolate and glycine accumulated, and only a trace of serine-(14)C was detected. Then glycolate and glycine were initially carboxyl-labeled, and glycolate became uniformly labeled almost immediately and before glycine. These results suggest rapid metabolism of glycolate and glycine, in addition to the glycolate pathway.